THE OCCURRENCE OF HAZARDOUS GEOCRYOLOGICAL PROCESSES IN THE CRYLITHOZONE OF RUSSIA - Garagulya L.S.; Gordeyeva G.I.; Yershov E.D.; Trush N.I. (My University, 1996)
The paper summarizes the results of research into the development of exogenous geological processes in the cryolithozone carried out at Moscow State University. The main types of modern geocryological processes are identified, and the natural and technogenic geocryological processes are classified according to their degree of hazard. The regions of Russia are assessed as to the dynamics of geocryological processes in the case of climatic warming, cooling and technogenic effects.